2004
DOI: 10.1590/s0328-03812004000400004
|View full text |Cite
|
Sign up to set email alerts
|

A peridomestic population of the tsetse fly Glossina palpalis palpalis Robineau-Desvoidy, 1830 (Diptera: Glossinidae) at Kontagora town, Niger state, Nigeria

Abstract: ResumoUma população peridoméstica de moscas tsetse Glossina palpalis palpalis Robineau-Desvoydy, 1830 (Diptera: Glossinidae) na cidade de Kontagora, estado de Niger, Nigéria -O artigo aborda alguns aspectos das populações peridomésticas das moscas tse-tsé Glossina palpalis palpalis Robinezu-Desvoidy, 1830 em Kontagora, Nigéria. Foi caracterizado um comportamento anormal deste vetor e que é de importância epidemiológica significante. Dados sobre a ecologia foram obtidos em 1995 e 1999. Os resultados indicam que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
3
5
1
Order By: Relevance
“…The species of tsetse flies we reported in our study were earlier reported in the same region by Karshima et al [ 23 ] and in other parts of Nigeria [ 24 , 25 ] and were among the first eleven species of tsetse flies reported in Nigeria [ 26 ]. Glossina palpalis was predominantly higher than G. tachinoides in line with earlier reports [ 25 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 86%
“…The species of tsetse flies we reported in our study were earlier reported in the same region by Karshima et al [ 23 ] and in other parts of Nigeria [ 24 , 25 ] and were among the first eleven species of tsetse flies reported in Nigeria [ 26 ]. Glossina palpalis was predominantly higher than G. tachinoides in line with earlier reports [ 25 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, this finding is in contrast to the finding of Ahmed (2004) who observed older population in Kontagora town, Nigeria.…”
Section: Discussioncontrasting
confidence: 99%
“…In this present study, the frequency of encounter of pregnancy stages of flies in the first and second instar larvae was same, hence contradict this order. A similar observation was made by Mohammed-Ahmed et al (1993) and Ahmed (2004).…”
Section: Discussionsupporting
confidence: 86%
“…The detection of Trypanosoma brucei trypanosomes in the current study is in agreement with Anene et al (16), who reported that Trypanosoma brucei is the predominant species involved in canine trypanosomiasis in Nigeria. The presence of trypanosomes in the study area can be attributed to factors such as the unrestricted movement of dogs through commercial purposes, hunting expeditions into endemic areas and existence of Glossina palpalis palpalis both in the wet and dry seasons in areas where hunting expeditions normally take place (17).…”
Section: Discussionmentioning
confidence: 99%
“…The people in the study area are predominantly crop farmers whose activities are restricted to the short period of rainfall. The long dry season is used mainly for hunting in which the expeditions takes them south, where tsetse flies abound (17). The study therefore investigated possible incursion of trypanosomes to the study area through dogs.…”
Section: Introductionmentioning
confidence: 99%